2022
DOI: 10.3389/fpsyg.2022.883157
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Quality of Life and Positive Psychological Resources in Cancer Patients: A Meta-Analysis

Abstract: PurposeThis study aimed to assess the evidence of the association between positive psychological resources and quality of life in patients with cancer.MethodsElectronic searching was performed to retrieve articles from PubMed, Web of Science, Embase, CNKI, and CBM (from inception to 7 April 2022). Summary correlation coefficient (r) values were extracted from each study, and 95% CIs were calculated by the random-effect model. Subgroup and sensitivity analyses were performed to investigate potential heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…In our study, we found a significant negative correlation between participants’ level of physical activity and their disease activity. This result suggests that a positive lifestyle and moderate physical exercise may have a beneficial impact on the management of Crohn’s disease, which is consistent with previous research findings [ 26 , 27 ]. Exercise can reduce the degree of inflammation in CD patients, increase their bone density, muscle mass, and aerobic capacity, improve their fatigue, psychological state, and quality of life [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found a significant negative correlation between participants’ level of physical activity and their disease activity. This result suggests that a positive lifestyle and moderate physical exercise may have a beneficial impact on the management of Crohn’s disease, which is consistent with previous research findings [ 26 , 27 ]. Exercise can reduce the degree of inflammation in CD patients, increase their bone density, muscle mass, and aerobic capacity, improve their fatigue, psychological state, and quality of life [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Statistics indicate that less than a third of Eastern Mediterranean breast cancer patients have a good quality of life, an integrated and multidimensional educational program is necessary to improve the quality of life of breast cancer patients 42 . There is evidence that breast cancer patients who have stronger social support have a higher resilience to stress and better quality of life 43,44 . This study explored how psychological distress impacts the quality of life in breast cancer patients, providing evidence that psychological intervention can enhance their happiness in life.…”
Section: Discussionmentioning
confidence: 99%
“… 42 There is evidence that breast cancer patients who have stronger social support have a higher resilience to stress and better quality of life. 43 , 44 This study explored how psychological distress impacts the quality of life in breast cancer patients, providing evidence that psychological intervention can enhance their happiness in life.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, building positive resources is key for well‐being (Schiavon et al, 2017). Multiple meta‐analyses and studies have demonstrated that optimism, or positive expectations of the future, is a significant predictor of depression and anxiety among individuals with cancer, heart disease, and multiple sclerosis (Fasano et al, 2020; Schiavon et al, 2017; Zhao et al, 2022). Guided imagery, positive storytelling, and strength‐based work help build optimism, which can enhance resiliency and well‐being (Park et al, 2013; Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple meta‐analyses and studies have demonstrated that optimism, or positive expectations of the future, is a significant predictor of depression and anxiety among individuals with cancer, heart disease, and multiple sclerosis (Fasano et al, 2020; Schiavon et al, 2017; Zhao et al, 2022). Guided imagery, positive storytelling, and strength‐based work help build optimism, which can enhance resiliency and well‐being (Park et al, 2013; Zhao et al, 2022). Although these processes hold promise for improving psychosocial outcomes, no studies, to date, have tested whether they serve as mechanisms of action in treatments for NF.…”
Section: Introductionmentioning
confidence: 99%